Dziewczyny do wzięcia . Ready to Get Married - Kondratiuk, Janusz Janusz Kondratiuk (Zespoły Filmowe Pryzmat, 1972)
Three girls from a village near Warsaw visit the capital on a Saturday to find entertainment and may be husbands. The expected boys do not show up on the station, but two other gentlemen try to pick them up. They go to a smart café and the boys buy them portions of cream. The girls do not like it, but consume it out of politeness. The men, who are obviously manual workers, pretend to have finished university and to work in an office. The five indulge in a game of mutual banter and daydream about love, affluence, consumption and urban lifestyle. An incident when one of the girls cannot take any more of the sweet cream gives the other two an excuse to eliminate her from the apparent competition for the boys. The boys take them to a friend’s flat and start flirting. But soon it turns out that it is the left-out girl who will find her “love”… or at least an illusion of it. A cult film, with amateur actors playing two of the girls and a superb soundtrack by Czesław Niemien, often compared to “Loves of a Blond” by Milos Forman.